Reactive Oxygen Species as a Response to Wounding: In Vivo Imaging in Arabidopsis thaliana - Prasad, Ankush; Sedlářová, Michaela; Balukova, Anastasiia; Rác, Marek; Pospíšil, Pavel (Frontiers in Plant Science, 2020)
Mechanical injury or wounding in plants can be attributed to abiotic or/and biotic causes. Subsequent defence responses are either local, i. e. within or in the close vicinity of affected tissue, or systemic, i. e. at distant plant organs. Stress stimuli activate a plethora of early and late reactions, from electric signals induced within seconds upon injury, oxidative burst within minutes, and slightly slower changes in hormone levels or expression of defence-related genes, to later cell wall reinforcement by polysaccharides deposition, or accumulation of proteinase inhibitors and hydrolytic enzymes. In the current study, we focused on the production of reactive oxygen species (ROS) in wounded Arabidopsis leaves. Based on fluorescence imaging, we provide experimental evidence that ROS [superoxide anion radical (O2•-) and singlet oxygen (1O2)] are produced following wounding. As a consequence, oxidation of biomolecules is induced, predominantly of polyunsaturated fatty acid, which leads to the formation of reactive intermediate, products and electronically excited species.